M-Commerce como uma estratégia de inovação na organização da feira de agricultores familiares de Paragominas – PA - CORDEIRO, Renato Rodrigues (2021)
The dissertation on the Fair of Family Farming of Paragominas - PA aimed to discover the potential of the municipal public policy to strengthen family farming in the city, aiming to improve living conditions, through the generation of work and income. Therefore, we tried to implement a mobile phone marketing application, characterized as M-Commerce, whose purpose is to contribute to innovation in the organizational structure of the Fair, in order to assist in the production and marketing management processes of family farming , based on the understanding that social transformations have generated dynamics operated through communication and language instruments, in which virtual networks create environments and mechanisms that can strengthen territorial development. The dissertation consists of three articles. In the first, we sought to understand family farming, particularly its production process, as a strategy for rural territorial development, as the production of food for the table of citizens of Paragominas comes, in part, from this segment, generating wealth and income distribution under solidarity economy principles. The second article describes the implementation of the “Hoje Tem Feira” Project as a municipal public policy action in Paragominas – Pa; The project aimed to strengthen the production and marketing process, by building a structure of services aimed at supporting family farmers in Paragominas, in the flow of production. The third article addresses the issue of innovation in the management of the family farming fair in Paragominas–PA, describes the process of structuring it as a social organization, passing through moments of training at the management level, associativism, cooperativism, solidarity economy and, finally, the applicability and a sales application, via M-commerce. For the beginning of the research, meetings were held to explain the research intentions, at which time a communication channel was established between the parties involved (researcher, market vendors, representatives of the Entrepreneur Room/Municipal Secretariats of Government of Paragominas, SEMAGRI and SEBRAE ), to define the responsibilities between these different subjects in carrying out the research and implementing M-commerce. The second phase consisted of data collection from primary sources, in addition to interviews with semi-structured questions, aiming to understand how marketers were organized from the production process to commercialization, in addition to their relationship with the buyers of their products. The “Today Has Fair Project” moves an amount of products with visible results. This action in 2020 generated an average monthly revenue of R$19,424.78, totaling approximately R$213,672.62 of annual income for that year. In 2019, earnings were around R$ 161,000.00, and it is possible to observe an increase in income based on the supply and demand of products, by marketers and buyers, respectively. Thus, it is concluded that the importance of open markets for the strengthening of Family Farming is undeniable, so that, through it, farmers have access to a market with fairer prices, both for them and for buyers.